Determining the location of Malaysia Airlines Flight MH370 - Pırtı, Atınç; Yucel, M. Ali; Hoşbaş, Ramazan Gürsel (Geodesy and Cartography, 2023)
Malaysia Airlines Flight 370, which was flying from Kuala Lumpur, Malaysia, to Beijing, China, lost communication with air traffic control shortly after take-off on March 8, 2014, and vanished. While the rest of the world awaited news of the missing plane and the 239 people on board, officials and experts began to look into the limited information available concerning the airliner’s real activities. The disappearance of a Malaysia Airline flight, carrying 239 passengers and crew, is one of the world’s biggest aviation mysteries. Despite all the efforts and evidence obtained so far, the crash site of Malaysia Airlines Flight MH370 could not be determined exactly. In this study, which we have done, the crash zone of the aircraft has been determined approximately by using the data in the previously prepared reports. In addition, the average ocean current speeds, directions and the parts of the debris of the aircraft were investigated on the satellite images, and the estimation of the area where the plane crashed was tried to be strengthened.